Lack of beneficial effects of platelet-rich plasma on sinus augmentation using a fluorohydroxyapatite or autogenous bone: An explorative study - Boworn Klongnoi (2018)
Background: Maxillary sinus augmentation is frequently necessary before placement of dental implants in the posterior maxilla. Besides autogenous bone graft, various bone substitutes have been used, with favourable results. Although platelet-rich plasma (PRP) has been used in the field of oral and maxillofacial surgery for years, its beneficial effects on osseous regeneration still remain unclear. The aim of this study was to evaluate the short and long time effects of PRP on single-stage sinus augmentation using autogenous bone or a fluorohydroxyapatite (Algipore®) in a randomized prospective animal study. Methods: After extraction of maxillary premolars of sixteen minipigs, the wounds were allowed to heal for 2 months. Then, sinus augmentations were performed bilaterally using one of the following grafting materials: autogenous bone and Algipore® with or without PRP. Three dental implants (Ankylos®) were installed in each sinus simultaneously. Four animals were euthanized at each period of observation (1, 2, 8 and 12 months). Implant-bearing specimens were sectioned bucco-lingually along the long axis of implants and undecalcified ground specimens were prepared. The bone-implant-contact (BIC) was measured by means of microradiographic examination. For histological evaluation, the specimens were stained with toluidin blue, and the percentage of the newly formed bone and the remaining bone substitute were evaluated. Results: The grafting materials chosen showed increasing levels of BIC and newly formed bone throughout the period of observation in both PRP and non-PRP groups. Adding PRP resulted in lower BIC and newly formed bone compared with autogenous bone grafts or Algipore® alone. However, a statistical significance was not found. The percentages of the remaining bone substitute in both the PRP and non-PRP groups were closely comparable in all observation periods. Conclusions: The application of PRP could not reveal significant beneficial effects on the BIC, the percentage of the newly formed bone and the remaining bone substitute in this study. © 2006 The Authors.